THE ADVANTAGES AND DISADVANTAGES OF E-LEARNING IN ENGLISH LESSON DURING COVID 19 PANDEMIC AT ADHYAKSA 2 JUNIOR HIGH SCHOOL - Kalinggoru, Alan Mardy; Hambandima, Erny Selfina Nggala (English Education Study Program - Artha Wacana Christian University, 2023)
The study of this research is entitled “Advantages and Disadvantages of E-Learning in English Lesson during Covid-19 Pandemic at Adhyaksa 2 Junior High School’’. The aim of this study is to find out the advantages and disadvantages of E-Learning in English Lesson during covid-19 pandemic at Adhyaksa 2 Junior High School. The method used is descriptive qualitative. The data collected from interviewed English Teacher and 15 students at 8 grade. The result shows that the teacher as the advantages easily to compile and deliver the material through Application without limitation of time. However, teacher has disadvantages in how to use and how to master E-Learning method due to Difficult to develop teaching material and feel fail to guide students to understand any material directly due to lack of socialization about E-Learning from Government. The students have th advantages in helping students to focus on learn independently, helping students easily to find English material and the answer of a task on the internet through Smartphone and helped students master in using electronical device for learning purposes. Moreover, E-Learning depends on electricity also good signal, created problems of opportunities for students to cheat freely on internet. This is force the parents to spend more budget for mobile data package per month.